Using the Wolfram|Alpha project to teach future mathematics teachers - T. H. Kramarenko; Yu. S. Lohvynenko (CTE Workshop Proceedings, 2013)
Among the most significant Internet projects in the field of computer mathematics are the Sage open-source computer mathematics project (http://www.sagemath.org/) and the Wolfram|Alpha project (http://www.WolframAlpha.com), which uses the Mathematica system of computer mathematics. The Wolfram|Alpha project was launched in 2009, and now has an audience of about 17 million users, according to statistics. Wolfram|Alpha is a representative of the family of online directories, so-called knowledge bases. Unlike conventional search engines, such services do not work with external resources, but with its own structured database. In addition, they do not provide a link to the source, but a direct answer to the question posed by the user. In other words, it is a means of so-called factorial search. Wolfram|Alpha features proprietary intelligent query parsing algorithms, strong direct computational capabilities, flexible results display, visualization and illustration tools, and a wide range of data export options.